Integration of spatial justice into navigating the combat on illegal, unreported and unregulated fishing in ocean and coastal areas - He, Yuru; Li, Yan; Li, Yanan; Zhu, Jiangfeng (Frontiers in Marine Science, 2024)
As a geographical dimension of justice, spatial justice is characterized by the interplay of social justice and heterogeneous spaces, including the ocean. Despite the generous contribution of ocean to humankind, concerns over aquatic spatial justice are disproportionately lacking. Among the core disruptors of ocean justice, illegal, unreported and unregulated (IUU) fishing imposes a major threat to global fisheries governance. The synthesis of spatial analysis and justice perspective can generate new insights to help understand and potentially address IUU fishing. To examine the spatial (in)justices concerning IUU fishing, we first propose a novel tripartite framework that envisions space as a form of opportunity, society and rights to externalize its socio-environmental implications. Then we integrate productive, distributive and consumptive justices to examine the spatial variations of IUU stakeholders along the fish value chain, and use stakeholder analysis to investigate spatial powers and conflicts regarding both a micro scale of fish communities, and a macro scale of states (coastal state, flag state, port state and market state) and supernational players (regional fisheries management organizations and marine protected areas). It is discovered that certain regions provide greater spatial benefits that stimulate IUU behaviors; IUU misconducts cause spatial differentiation and spatial deprivation that disrupt social orders in fish communities; space can empower stakeholders’ inclusive and proper engagement into the place-based management process against IUU fishing. Since the spatialized vision has been increasingly highlighted in marine fisheries management, it is suggested to intervene in the world ocean by leveraging spatial knowledge, managing spatial conflicts and facilitating spatial action, in order to promote spatial justice and better combat IUU fishing globally.